Hakikat Bahasa dalam Objek Kajian Linguistik - Dina Adzkia Izzanti; Muhammad Rizky Nasution; Habib Abdul Wasik; Muhammad Ilham Juanda; Sahkholid Nasution (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Language as an object of linguistic study is an arbitrary sound symbol system used by members of a social group to cooperate, communicate, and identify themselves. Language has several characteristics or properties as follows: Language is a system, Language is in the form of symbols, Language is sound, Language is meaningful, Language is arbitrary, Language is conventional, Language is productive, Language is unique besides being universal, Language is dynamic, and Language is humane and varied. One of the advantages of humans is the intellect that is inherent in every human being. Human intellect can be used and empowered with the help of language. Including in everyday life, anyone or anywhere, humans as social beings cannot avoid the use of language, either in writing or orally. As a linguistic science, linguistics has experienced stages of development like other sciences, the stages of development in question include; the stage of speculation, the stage of observation and classification, and the stage of formulating theories. The method used in this article is a literature study, with data collection from various sources such as books, journals, and existing research. The data is analyzed critically to support research propositions and ideas.